Glasnost: Enabling End Users to Detect Traffic Differentiation - Dischinger, Marcel; Marcon, Massimiliano; Guha, Saikat; Gummadi, Krishna; Mahajan, Ratul; Saroiu, Stefan (Proceedings of 7th USENIX Symposium on Networked Systems Design and Implementation (NSDI), 2010)
Holding residential ISPs to their contractual or legal obligations of “unlimited service” or “network neutrality” is hard because their traffic management policies are opaque to end users and governmental regulatory agencies. We have built and deployed Glasnost, a system that improves network transparency by enabling ordinary Internet users to detect whether their ISPs are differentiating between flows of specific applications. We identify three key challenges in designing such a system: (a) to attract many users, the system must have low barrier of use and generate results in a timely manner, (b) the results must be robust to measurement noise and avoid false accusations of differentiation, which can adversely affect ISPs’ reputation and business, (c) the system must include mechanisms to keep it up-to-date with the continuously changing differentiation policies of ISPs worldwide. We describe how Glasnost addresses each of these challenges. Glasnost has been operational for over a year. More than 350,000 users from over 5,800 ISPs worldwide have used Glasnost to detect differentiation, validating many of our design choices. We show how data from individual Glasnost users can be aggregated to provide regulators and monitors with useful information on ISP-wide deployment of various differentiation policies.